Evaluation of the Reality of Sports Activities at Tishreen University A Field Study - سلهب, عمار; وائل مارون معوض,; خلود نزار علي ديب , (Latakia University Journal -Medical Sciences Series, 2023)
The research aimed to evaluate the reality of sports activities at Tishreen University in terms of human and material resources, sports equipment and facilities, and the effectiveness of the applied administrative system. The research relied on the analytical descriptive approach, and the research community included all student leaders responsible for sports activity, administrative supervisors, coaches, referees, and members of the educational staff in the College of Physical Education at the university, who numbered (133) individuals, as the researcher adopted the comprehensive enumeration method, and the size of the basic sample was (98) individuals, after excluding (40) individuals for the purposes of the exploratory study. The results showed that the reality of sports activities with regard to the two dimensions of human resources and the administrative system in general is an acceptable reality, while the reality of sports activities with regard to the dimensions of financial resources and sports equipment and facilities in general is a bad reality.